2014
DOI: 10.1007/s11999-014-3810-8
|View full text |Cite
|
Sign up to set email alerts
|

Does Advanced Cryotherapy Reduce Pain and Narcotic Consumption After Knee Arthroplasty?

Abstract: Level II, therapeutic study. See the Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
36
3
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 22 publications
6
36
3
14
Order By: Relevance
“…Patients feel less medicated and have a better postoperative course. Advanced cryotherapy was compared with icing only in the post operative course of TKA in a randomized controlled trial [4]. The authors concluded that there were no advantages in using advanced cryotherapy in daily practice, particularly because of the additional cost associated with these systems.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients feel less medicated and have a better postoperative course. Advanced cryotherapy was compared with icing only in the post operative course of TKA in a randomized controlled trial [4]. The authors concluded that there were no advantages in using advanced cryotherapy in daily practice, particularly because of the additional cost associated with these systems.…”
Section: Discussionmentioning
confidence: 99%
“…These side effects do not come into play when using CDIC. Thienpont et al [4] bring up the risk of frostbite in the area where CDIC is applied. This is an extremely serious complication that would require an additional major soft tissue procedure [23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations